Subsidies, financial constraints and firm innovative activities in emerging economies - Mateut, Simona (Springer, 2017)
This paper investigates the relationship between public subsidies and firm innovation in emerging economies, which are likely to have less developed financial markets. Innovation includes the introduction of new products or services and the upgrade of existing ones, which is of particular relevance for these economies. The results obtained using alternative measures of financial constraints and market competition, within a range of econometric techniques, suggest a positive relation between public subsidies and the innovative activities of 11,998 firms across thirty Eastern Europe and Central Asia countries. This correlation is stronger for firms more likely to be financially constrained.